Hunting practices in southwestern Amazonia: a comparative study of techniques, modalities, and baits among urban and rural hunters - Marcela Alvares Oliveira; Franciany Braga-Pereira; Hani Rocha El Bizri; Thais Queiroz Morcatty; Carolina Rodrigues da Costa Doria; Mariluce Rezende Messias (BMC, 2023)
Abstract Background Hunting is a vital means of obtaining animal in various human populations. Hunters rely on their knowledge of species ecology and behavior to develop and employ hunting techniques and increase their chances of success. The comparison of the hunting practices of different human societies can shed light on the sustainability of hunting and the impact it has on species' populations. In this study, we examine and compare the techniques, modalities, and baits used by urban and rural hunters in Rondônia, a state in southwestern Amazonia, Brazil. We expected that rural hunters would use these elements and have greater knowledge when compared to urban hunters. We also expect that the use of specific hunting techniques and modalities will have greater selectivity and specificity of capture for rural hunters and that this knowledge will differ between groups. Methods We conducted 106 semi-structured interviews with rural and urban hunters from October 2018 to February 2020. We analyzed the data using PERMANOVA and Network analyses to compare and contrast the hunting practices of each group. Results We recorded four main hunting techniques divided into ten modalities with three techniques and seven modalities being the preferred choices among hunters. Waiting for at a Fruit Tree was cited as the primary technique employed by hunters living in urban and rural areas indicated. While the techniques and modalities were similar among hunters, the composition of species targeted and baits used differed between groups. Our network approach showed that modularity in urban areas was numerically lower than in rural areas. All species had one to more techniques associated with their capture. Conclusions Hunters living in urban and rural environments showed high similarity in their practices, probably due to sharing similar environments to hunt containing similar species, as well as targeting preferably the same species.